2020
DOI: 10.3390/jcm9020537
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Behaviors and Metabolic Syndrome in Schizophrenia Patients

Abstract: The metabolic syndrome (MS) is highly prevalent in schizophrenia patients, resulting from both pharmacotherapy and their lifestyle. To avoid its development, the analysis of patients’ eating behaviors followed by the necessary nutritional changes should become a routine element of treatment. The aim of this study is to investigate the effect of dietary habits on the course of schizophrenia and MS, cognitive performance, symptom severity, and subjective assessment of eating behaviors in schizophrenia patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Moreover, nutritional deficiencies are identified as risk factors for psychiatric disorders [ 283 ]. Patients were more likely to have an irregular eating schedule, eat instant meals, and drink more coffee than controls in a study of 194 subjects [ 284 ]. People with schizophrenia also smoke four more cigarettes per day on average than controls [ 284 ].…”
Section: Role Of Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, nutritional deficiencies are identified as risk factors for psychiatric disorders [ 283 ]. Patients were more likely to have an irregular eating schedule, eat instant meals, and drink more coffee than controls in a study of 194 subjects [ 284 ]. People with schizophrenia also smoke four more cigarettes per day on average than controls [ 284 ].…”
Section: Role Of Quality Of Lifementioning
confidence: 99%
“…Patients were more likely to have an irregular eating schedule, eat instant meals, and drink more coffee than controls in a study of 194 subjects [ 284 ]. People with schizophrenia also smoke four more cigarettes per day on average than controls [ 284 ]. Finally, a study of 159 patients with schizophrenia found 41% did not eat fruit daily, 51% ate meals in less than fifteen minutes, and 63% did not consume fish [ 285 ].…”
Section: Role Of Quality Of Lifementioning
confidence: 99%
“…They found that 13.2% of subjects exhibited abnormal feeding behaviors, which was associated with more severe positive symptoms [ 39 ]. Similarly, in a study on a sample of 87 schizophrenia patients, Adamowicz and Kucharska-Mazur indicated that less severe positive symptoms were associated with healthier eating behaviors [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results are fully consistent with those of the previously conducted studies that have shown poor dietary habits among patients with schizophrenia [ 10 , 20 , 21 ]. The vast majority of the available studies compared dietary habits of patients with schizophrenia to the general population; while only two, according to our knowledge, examined the differences in their dietary habits depending on MetS presence [ 22 , 23 ]. In the mentioned studies, and similar to our findings, dietary habits of those participants with and without MetS were very similar, even though it was assumed that they would significantly differ.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, as reported by Parletta et al [ 10 ], people with serious mental illness in the Western countries tend to consume significantly lower amounts of high-quality foods, while unhealthy foods are consumed in higher amounts. Despite the aforementioned studies, and to the best of our knowledge, only two previous studies compared dietary habits of patients with schizophrenia with and without MetS, and found no significant differences [ 22 , 23 ], except for some of the applied culinary methods [ 23 ].…”
Section: Introductionmentioning
confidence: 99%